2014
DOI: 10.1097/jim.0000000000000107
|View full text |Cite
|
Sign up to set email alerts
|

Association of Methylenetetrahydrofolate Reductase Gene C677T Polymorphism with Multiple Sclerosis in Turkish Patients

Abstract: These results showed that T allele of C677T polymorphism was associated with MS susceptibility in Turkish population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Yang et al (2014) also reported in a meta-analysis a good association of MTHFR C677T mutation with the risk of hypertension between Asians, Chinese, and Caucasians subjects. Similar findings were obtained in the population of Turkey (Cevik et al, 2014). On the other hand, many authors reported that MTHFR C677T polymorphism was independent factor of essential hypertension in different ethnic populations (Ilhan et al, 2008;Heux et al, 2004;Qian et al, 2007) as well as of diastolic hypertension manifested in pregnant women (Kosmas et al, 2004).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Yang et al (2014) also reported in a meta-analysis a good association of MTHFR C677T mutation with the risk of hypertension between Asians, Chinese, and Caucasians subjects. Similar findings were obtained in the population of Turkey (Cevik et al, 2014). On the other hand, many authors reported that MTHFR C677T polymorphism was independent factor of essential hypertension in different ethnic populations (Ilhan et al, 2008;Heux et al, 2004;Qian et al, 2007) as well as of diastolic hypertension manifested in pregnant women (Kosmas et al, 2004).…”
Section: Resultssupporting
confidence: 67%
“…MTHFR gene has been studied more frequently in relation to homocysteine and folate metabolism, with regard to a variety of disorders including CVD and Hypertension (Javed et al, 2012). MTHFR and the hypertension risk have been discussed by several investigators with conflicting results (Ilhan et al, 2008;Cevik et al, 2014;Heux et al, 2004;Qian et al, 2007;Kosmas et al, 2004;Yang et al, 2014;Markan et al, 2007). Many previous studies have implicated that the MTHFR vari-ants C677T and A1298C have been a risk factor for Essential Hypertension (Ilhan et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…SAM methylates MBP at arginine sites within the protein, which protects MBP against degradation and is hence important for maintaining the integrity of the myelin sheath [ 46 ]. Common genetic variants in MTHFR have already been associated with the risk for MS development in multiple populations [ 47 , 48 , 49 , 50 ]. PLK1 also inhibits the protein complex MTORC1, which in turn is an important positive regulator of (re)myelination by ODCs [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…SAM methylates MBP at arginine sites within the protein, which protects MBP against degradation and is hence important for maintaining the integrity of the myelin sheath 51 . Common genetic variants in MTHFR have already been associated with the risk for MS development in multiple populations [52][53][54][55] . PLK1 also inhibits the protein complex MTORC1, which in turn is an important positive regulator of (re)myelination by ODCs 56,57 .…”
Section: Discussionmentioning
confidence: 99%